(untitled) (International Journal of Medical and Surgical Sciences, 2014)
The World Medical Association (WMA) has developed the Declaration of Helsinki as a statement of ethical principles for medical research involving human subjects, including research on identifiable human material and data. It has undergone numerous revisions and amendments, the most recent being in Fortaleza–Brazil (2013). This new version includes various improvements and modifications which substantially easier to read, with a greater number of subsections. It is emphasized that the research ethics committee is recognized as a fundamental part of the research, the importance of disseminating research and compulsory informed consent. The Declaration of Helsinki is constantly evolving, and is arguably a document that provides the basis for the undertaking of any research. His knowledge and reading, is mandatory for all health professionals.